Enhanced anti-biofilm and anti-caries potential of arginine combined with calcium glycerophosphate and fluoride - Miranda, Marina Lins [UNESP]; Danelon, Marcelle [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Kopp, Willian [UNESP]; Nunes, Gabriel Pereira [UNESP]; Brighenti, Fernanda Lourenção [UNESP] (Elsevier, 2024)
Objective: The aim of this work was to evaluate the antibiofilm and anticaries properties of the association of arginine (Arg) with calcium glycerophosphate (CaGP) and fluoride (F). Methods: An active attachment, polymicrobial biofilm model obtained from saliva and bovine teeth discs were used. After the initial biofilm growth period, the enamel discs were transferred to culture medium. The treatment solutions were added to the culture media to achieve the desired final concentration. The following groups were used: negative control (Control); F (110 ppm F); CaGP (0.05 %); Arg (0.8 %) and their associations (F + CaGP; Arg + F; Arg + CaGP; Arg +F + CaGP). The following analyses were carried out: bacterial viability (total bacteria, aciduric bacteria and mutans streptococci), pH assessment of the spent culture medium, dry weight quantification, evaluation of surface hardness loss (%SH) and subsurface mineral content. Normality and homoscedasticity were tested (Shapiro-Wilk and Levene's test) and the following tests were applied: two-way ANOVA (acidogenicity), Kruskall-Wallis (microbial viability) and one way ANOVA (dry weight, %SH, mineral content). Results: The association Arg + F + CaGP resulted in the lowest surface hardness loss in tooth enamel (-10.9 ± 2.3 %; p < 0.05). Arg +F + CaGP exhibited highest values of subsurface mineral content (10.1 ± 2.9 gHAP/cm3) in comparison to Control and F (p < 0.05). In comparison to Control and F, Arg +F + CaGP promoted the highest reduction in aciduric bacteria and mutans streptococci (5.7 ± 0.4; 4.4 ± 0.5 logCFU/mL, p < 0.05). Conclusions: The Arg-F-Ca association demonstrated to be the most effective combination in protecting the loss of surface hardness and subsurface mineral content, in addition to controlling important virulence factors of the cariogenic biofilm. Clinical significance: Our findings provide evidence that the Arg-F-Ca association showed an additive effect, particularly concerning protection against enamel demineralization. The combination of these compounds may be a strategy for patients at high risk of caries.
Keywords: Arginine; Biofilms; Calcium glycerophosphates; Dental caries; Fluorides